Identification of Chebulinic Acid and Chebulagic Acid as Novel Influenza Viral Neuraminidase Inhibitors - Li, Ping; Du, Ruikun; Wang, Yanyan; Hou, Xuewen; Wang, Lin; Zhao, Xiujuan; Zhan, Peng; Liu, Xinyong; Rong, Lijun; Cui, Qinghua (Frontiers in Microbiology, 2020)
Inﬂuenza A virus (IAV) causes seasonal epidemics and occasional but devastating pandemics, which are of a major public health concern. Although several antiviral drugs are currently available, there is an urgent need to develop novel antiviral therapies with different mechanisms of action due to emergence of drug resistance. In this study, two related compounds, chebulagic acid (CHLA) and chebulinic acid (CHLI), were identified as novel inhibitors against IAV replication. A reporter virus-based infection assay demonstrated that CHLA and CHLI exhibit no inhibitory effect on IAV entry or RNA replication during virus replication cycle. Results of viral release inhibition assay and neuraminidase inhibition assay indicated that CHLA and CHLI exert their inhibitory effect on the neuraminidase-mediated viral release. Moreover, oseltamivir-resistance mutation NA/H274Y of NA is susceptible to CHLA or CHLI, suggesting a different mechanism of action for CHLA and CHLI. In summary, CHLA and CHLI are promising new NA inhibitors that may be further developed as novel antivirals against influenza A viruses.